The Role of Brand Love in Mediating the Influence of Brand Image and Customer Experience on Consumer Loyalty of Pond’s Cosmetics (A Study Among Students of the University of Mataram) - Elisa Budiarti; Muhammad Mujahid Dakwah (LP2M IAIN Palopo, 2025)
This study analyzes brand love's mediating role in the relationship between brand image and customer experience on consumer loyalty toward Pond's Whitening Cream among University of Mataram students. The cosmetics industry in Indonesia demonstrates rapid growth at 5.35% annually, yet Pond's market share declined significantly from 25.3% in 2023 to 9.5% in 2024, necessitating comprehensive consumer behavior investigation. This quantitative research employed an explanatory design with 150 respondents selected through purposive sampling. Data were collected via online questionnaire utilizing a five-point Likert scale encompassing 19 items across four constructs: brand image, customer experience, brand love, and consumer loyalty. Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 3.0 software analyzed the data through outer and inner model evaluation, incorporating 5,000 bootstrap permutations. Results demonstrate that brand image exerts the strongest direct effect on brand love (β = 0.567, p = 0.000), while customer experience demonstrates lesser influence (β = 0.328, p = 0.001). Both variables maintain significant direct pathways to consumer loyalty (β = 0.420 and β = 0.194 respectively). Critically, brand love mediates both relationships with substantial effect magnitude (β = 0.328, p = 0.000). The study concludes that brand love functions as a pivotal mediating mechanism, with brand image representing the paramount antecedent for emotional brand attachment. Future research should incorporate longitudinal designs, expand sample composition to non-academic populations, and investigate supplementary mediating variables including brand authenticity and perceived value.